DETERMINANT FACTOR OF LISTENER LOYALTY TO POP FM JAKARTA - Sehpudin, Agung; Fachrodji, Achmad (Dinasti International Journal of Digital Business Management, 2020)
This study aims to analyze the influence of radio programs, broadcasters and transmitter power on listening to Pop FM radio Jakarta and listeners loyalty. Primary data were obtained from questionnaires and secondary data were obtained from field research such as interviews with companies. The population of this study were all listeners of Pop FM Jakarta radio in Jabodetabek in May-June with a total sample of 210 people. The analytical method used is the LISREL version 8.80 Structural Equation Modeling (SEM). The results showed that radio programs, broadcasters and transmitter power had a significant positive effect on interest in listening to radio. Meanwhile, radio programs, broadcasters and transmitter power also have a significant positive effect on radio listeners' loyalty. The R Square value is 0.75 that in this study the broadcast program variables, announcers and transmitter power contributed 75%, the rest was influenced by other variables by 25%